THE UK’S REFERENDUMS DURING ITS INTEGRATION INTO THE EU (1973-2016) - Van, Chu Thanh (VNU Journal of Foreign Studies, 2020)
Throughout the UK’s integration into the EU (1973-2016), referendums were considered and used as an effective political tool for the Government to negotiate with the common people on important issues. During the period of 43 years, the Government called for their practices 12 times with an uneven frequency between the UK’s leaders, namely the UK’s Prime Ministers. One important notice is that among the 12 referendums, only two have direct links to the relationship between the UK and the EU. This article looks into the use of referendums in the UK in general and the two that are directly related to the EU in particular in the period of 1973-2016. Its conclusion and findings are expected to help outline the usage of this political tool in the contemporary and futuristic climax of the country.